2014
DOI: 10.1097/sla.0b013e31827da6c9
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Policy Development to Increase Split-Liver Transplantation for 2 Adult Recipients

Abstract: AASLT should be considered a surgical option for selected smaller-sized adults only in experimental clinical studies in experienced centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
69
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 37 publications
2
69
0
Order By: Relevance
“…The growing discrepancy between the number of available organs and the number of liver transplant candidates is an incentive for innovative surgical techniques such as split‐graft LT. If the split technique is well accepted for children, who lack size‐matched organs, fears of inferior results in adults still persist . The splitting procedure is associated with supposed or real challenges: a small‐for‐size graft, a cut surface prone to leaks and more difficult vascular and biliary reconstructions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The growing discrepancy between the number of available organs and the number of liver transplant candidates is an incentive for innovative surgical techniques such as split‐graft LT. If the split technique is well accepted for children, who lack size‐matched organs, fears of inferior results in adults still persist . The splitting procedure is associated with supposed or real challenges: a small‐for‐size graft, a cut surface prone to leaks and more difficult vascular and biliary reconstructions.…”
Section: Discussionmentioning
confidence: 99%
“…Aseni et al . reported a lower patient and graft survival rate in adults with split‐graft vs whole‐graft recipients, but focusing on full‐right and full‐left grafts, a fact which might lead to different outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty percent of patients in Europe and 14% in the United States die while waiting for a liver [1]. One possible way to reduce the waiting list mortality is splitting full livers into hemilivers; this procedure would allow transplantation in 2 adult recipients by using a single organ from a deceased donor.…”
mentioning
confidence: 99%
“…Aseni et al[28] reported a recent Italian multicenter experience of hemiliver SLT, showing inferior 5-year survival compared to whole liver transplantation (63% vs 83%). However, under certain circumstances, long-term survival after hemiliver SLT is equivalent to whole liver transplantation or LDLT[9,10,12,29].…”
Section: Discussionmentioning
confidence: 99%